Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah (BOS) Madrasah di Kantor Wilayah Kementerian Agama Provinsi Sumatera Utara - Lidya Lestari; Waizul Qarni (VISA: Journal of Vision and Ideas, 2022)
This study expects to make proper upgrades and augment viewpoints in the administration of BOS assets to make work solace and ideal execution of madrasas, particularly in the space of ​​​​the Office of the Service of Religion of the area of North Sumatra. The positive side of overseeing BOS assets should be visible from the degree of planning, execution cycle, and post-execution exercises, their subsidiary effects, and general assessment of the presentation of the Madsarah BOS Group. Second, BOS reserves emphatically affect working on the nature of madrasas, which is quantifiable with marks of expanding madrasah authorization status, expanding the quantity of understudies, and the quantity of understudies avoiding class and dropping with regard to school. The positive effect of BOS is additionally recorded from the way that the history of madrasa understudies' accomplishments in numerous and changed rivalries. Also, BOS reserves can increment school ethos and understudies' excitement for learning. Keywords: Effectiveness, BOS Fund